POCER 1927: Microencapsulation by Spray Drying Enhanced Powder Recovery and Mangiferin Stability of Phaleria macrocarpa’s Extracts - Lim, Yee Peng; Pang, Sook Fun; M. M., Yusoff; Siti Kholijah, Abdul Mudalip; Jolius, Gimbun (University of Nottingham, 2019)
A microencapsulation via spray-drying was evaluated for encapsulation of mangiferin extracted from Phaleria macrocarpa. The microencapsulation was performed using maltodextrin, whey protein isolate and a mixture of these components in a ratio of 9:1. The mangiferin was quantified using an ultra performance liquid chromatography coupled to the tunable UV detector and quadrupole time of flight mass spectrometer (UPLC TUV QTOF MS) and high performance liquid chromatography with diode array UV detector. It was found that encapsulation with maltodextrin yielded the lowest moisture content (7.3%) and yielded the highest powder yield (38.6%).